Elevated serum levels of anti-collagen type I antibodies in patients with spontaneous cervical artery dissection and ischemic stroke: a prospective multicenter study - Zimmermann, Silke; Weißenfels, Markus; Krümmer, Norma; Härtig, Wolfgang; Weise, Gesa; Branzan, Daniela; Michalski, Dominik; Pelz, Johann Otto (Frontiers in Immunology, 2024)
Introduction: Spontaneous cervical artery dissection (sCAD) is a rare vasculopathy whose trigger is still unknown. We hypothesized that autoimmunity against components of the vascular wall might play a critical role in sCAD, and examined anti-collagen type I antibodies in patients with sCAD, acute ischemic stroke, patients with thromboendarterectomy, and controls. Methods: Fifty-seven patients with sCAD (age 45.7±10.2 years, female 18 (31.6%)) were prospectively enrolled in four German stroke centers. Blood samples were collected at baseline, at day 10±3, and after 6±1 months. Patients with ischemic stroke not related to CAD (n=54, age 56.7±13.7 years, female 15 (27.8%)), healthy probands (n=80, age 57.4±12.9 years, female 56 (70%)), and patients undergoing thromboendarterectomy of the carotid artery (n=9, age 70.7±9.3 years, female 2 (22.2%)) served as controls. Anti-collagen type I antibodies were determined by enzyme-linked immunosorbent assays (ELISAs). Results: Patients with acute sCAD had higher serum levels of anti-collagen type I antibodies (33.9±24.6 µg/ml) than probands (18.5±11.0 µg/ml; p <0.001) but lower levels than patients with ischemic stroke not related to sCAD (47.8±28.4 µg/ml; p=0.003). In patients with sCAD, serum levels of anti-collagen type I antibodies were similar in the acute, subacute, and chronic phase. Levels of anti-collagen type I antibodies significantly correlated with circulating collagen type I (rho=0.207, p=0.003). Conclusion: Anti-collagen type I antibodies seem not to represent a trigger for acute sCAD or ischemic stroke but may rather be linked to the metabolism and turnover of collagen type I.